The Stories Clinicians Tell: Achieving High Reliability and Improving Patient Safety - Cohen, Daniel L (Perm J, 2016)
The patient safety movement has been deeply affected by the stories patients have shared that have identified numerous opportunities for improvements in safety. These stories have identified system and/or human inefficiencies or dysfunctions, possibly even failures, often resulting in patient harm. Although patients’ stories tell us much, less commonly heard are the stories of clinicians and how their personal observations regarding the environments they work in and the circumstances and pressures under which they work may degrade patient safety and lead to harm. If the health care industry is to function like a high-reliability industry, to improve its processes and achieve the outcomes that patients rightly deserve, then leaders and managers must seek and value input from those on the front lines—both clinicians and patients. Stories from clinicians provided in this article address themes that include incident identification, disclosure and transparency, just culture, the impact of clinical workload pressures, human factors liabilities, clinicians as secondary victims, the impact of disruptive and punitive behaviors, factors affecting professional morale, and personal failings.